A single-cell atlas of human and mouse white adipose tissue - Emont, Margo P.; Jacobs, Christopher; Essene, Adam L.; Pant, Deepti; Tenen, Danielle; Colleluori, Georgia; Di Vincenzo, Angelica; Jørgensen, Anja M.; Dashti, Hesam; Stefek, Adam; McGonagle, Elizabeth; Strobel, Sophie; et al. (Nature (London), 2022)
White adipose tissue, once regarded as morphologically and functionally bland, is now recognized to be dynamic, plastic and heterogenous, and is involved in a wide array of biological processes including energy homeostasis, glucose and lipid handling, blood pressure control and host defence 1 . High-fat feeding and other metabolic stressors cause marked changes in adipose morphology, physiology and cellular composition 1 , and alterations in adiposity are associated with insulin resistance, dyslipidemia and type 2 diabetes 2 . Here we provide detailed cellular atlases of human and mouse subcutaneous and visceral white fat at single-cell resolution across a range of body weight. We identify subpopulations of adipocytes, adipose stem and progenitor cells, vascular and immune cells and demonstrate commonalities and differences across species and dietary conditions. We link specific cell types to increased risk of metabolic disease and provide an initial blueprint for a comprehensive set of interactions between individual cell types in the adipose niche in leanness and obesity. These data comprise an extensive resource for the exploration of genes, traits and cell types in the function of white adipose tissue across species, depots and nutritional conditions. A single-cell atlas of white adipose tissue from mouse and human reveals diverse cell types and similarities and differences across species and dietary conditions.